Acute Gastroenteritis and Bronchopneumonia in an incompletely Immunized Infant – Case Report - Ikhsani, Alyza Syafrita; Sumarni, Neni (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Acute gastroenteritis (GEA) is gastrointestinal disease whose signs and symptomps are diarrhea, anorexia, vomiting, abdominal pain and fever. This condition is very common in children. Bronchopneumonia is a patchy inflammation of the lungs (exceeding one or two lobes) where exudate from white blood cells accumulates in the bronchi and bronchioles with spread to adjacent alveoli. Immunization can reduce the risk of the two diseases. This study will comprehensively discuss the relationship between incomplete immunization and the occurrence of ARI and bronchopneumonia in order to enable appropriate management. The method involves conducting a literature review by gathering literature from books and articles published in the last 10 years. We report a case of GEA along with bronchopneumonia in an infant aged 4 months 26 days with a history of incomplete immunization. Catch-up immunization should be carried out in all babies with a history of incomplete immunization to reduce the risk and severity of subsequent.